REHABILITATION OF ALVEOLAR BONE THROUGH GUIDED TISSUE REGENERATION WITH AUTOGENOUS BONE AND XENOGRAFTS: CBCT STUDY - Tibeică (Iordan); Tibeică Silviu Cătălin; Costuleanu Marcel; Agop-Forna Doriana; Forna Norina (Romanian Society of Oral Rehabilitation, 2024)
The aim of the study was to assess the bone gain achieved through guided bone regeneration (GBR) techniques using bovine-origin xenograft versus porcine-origin xenograft combined with autogenous bone. Materials and method. The study was conducted on 62 patients (28 male; 34 female), aged between 40-79 years. All patients had partial edentulousness and were candidates for dental implants and the rehabilitation of the resorbed alveolar bone through guided tissue regeneration (GTR) techniques. The characteristics of the study groups are presented in Tables 1.1-1.2. Based on the type of graft material used, the patients were divided into two study groups: bovine-origin xenograft + autogenous bone group (30 patients; 41 implant sites); porcine-origin xenograft + autogenous bone group (32 patients; 50 implant sites). The CBCT examination (Sirona Orthophos XG) was used to measure alveolar bone parameters (preoperatively and six months postoperatively): height, width, and osteodensity of the alveolar bone at the implant sites. Results. The average vertical bone gain (height) was lower in alveolar sites reconstructed with bovine-origin xenografts combined with autogenous bone (5.3076 mm) compared to those reconstructed with porcine-origin xenografts combined with autogenous bone (5.8736 mm). The average horizontal bone gain (width) was higher in alveolar sites reconstructed with bovine-origin xenografts combined with autogenous bone (4.4273 mm) compared to those reconstructed with porcine-origin xenografts combined with autogenous bone (4.1624 mm). The osteodensity gain was higher in alveolar sites reconstructed with bovine-origin xenografts combined with autogenous bone (279.59 HU) compared to those reconstructed with porcine-origin xenografts combined with autogenous bone (254.24 HU). Conclusions. Post-operative bone gain in vertical and horizontal dimensions, as well as osteodensity, were statistically significant both in the overall group and for each of the investigated categories (sex, age group, location). The use of guided bone regeneration technique using combination of xenografts with autogenous bone are effective in the reconstruction of alveolar bone.